NUTRITION AS A RISK FACTOR OF CHILD LEPROSY IN GRESIK DISTRICT 2019 - Isnaniyanti Fajrin Arifin; Flora Ramona Sigit Prakoeswa; Cita Rosita Sigit Prakoswa; Kohar Hari Santoso; Budi Utomo; Trias Mahmudiono; Agus Sri Wardoyo (Universitas Airlangga, 2022)
Background: Indonesia's annual increase in leprosy is a serious health problem. In east Java, child leprosy cases spread in several counties/cities, the number of new cases of child leprosy cases has been raised in Gresik District from 2015 until 2019. Purpose: This study analyzed characteristics, BCG vaccine status, nutritional status and home environment, the correlated risk factors to child leprosy in Gresik District. Methods: This study used a design population-based matched case-control design and analysis data using computer computing. The variables for this research were characteristics (age, sex, and education) and BCG vaccine status (BCG scar and without BCG scar), nutritional status classified as Body Mass Index (BMI)(normal and thin) and protein (albumin and Hb serum), and home environment (wall, ceiling, floor, humidity, ventilation, and density of occupancy). It was conducted in October 2019-February 2020 using a questionnaire, observation and measurements. The total sample was 36 respondents, of which the number of the case was 18, and the control was 18. Data were analyzed using the Logistic Regression method entered with a 95% CI and an OR. Results: Home environment had not correlated to leprosy cases of children. The completeness of BCG vaccine status correlated to children's leprosy cases (p=0.02). BMI had correlated to leprosy cases of children (p=0.01). The most influential variable was the completeness protein of albumin serum (Odds Ratio (OR) =9.10; 95%CI=1.11-41.44; p=0.01). Conclusion: The most dominant risk factor correlated with the incidence of leprosy is the serum albumin level.